Cancer Therapy: Harnessing the Formation of Natural Killer–Tumor Cell Immunological Synapses for Enhanced Therapeutic Effect in Solid Tumors (Adv. Mater. 22/2020). Issue 22 (2nd June 2020) - Im, Sooseok; Jang, Donghyun; Saravanakumar, Gurusamy; Lee, Junseok; Kang, Yeoul; Lee, Yeong Mi; Lee, Jaehyun; Doh, Junsang; Yang, Zung Yoon; Jang, Myoung Ho; Kim, Won Jong
Abstract : In article number 2000020, Won Jong Kim and co‐workers describe a reinforced natural killer (ReNK) system, adopting the formation of NK–tumor cell immunological synapses (IS) as a trigger for delivery of tumor‐specific chemotherapeutics. NK cells are decorated with the IS environment‐responsive micellar system to ensure the release of drug when they attack cancer cells. The strategy enables the NK cells to inhibit the growth of solid tumors by efficient penetration of the delivered drug into the tumor tissue; otherwise, its penetration is hindered by the dense extracellular matrix of the tumor tissue.